Comparison of a VR Stylus with a Controller, Hand Tracking, and a Mouse for Object Manipulation and Medical Marking Tasks in Virtual Reality - Hanna-Riikka Rantamaa; Jari Kangas; Sriram Kishore Kumar; Helena Mehtonen; Jorma Järnstedt; Roope Raisamo (Applied Sciences, 2023)
In medical surgery planning, virtual reality (VR) provides a working environment, where 3D images of the operation area can be utilized. VR allows 3D imaging data to be viewed in a more realistic 3D environment, reducing perceptual problems and increasing spatial understanding. In the present experiment, we compared a mouse, hand tracking, and a combination of a VR stylus and a grab-enabled VR controller as interaction methods in VR. The purpose was to investigate the suitability of the methods in VR for object manipulation and marking tasks in medical surgery planning. The tasks required interaction with 3D objects and high accuracy in the creation of landmarks. The combination of stylus and controller was the most preferred interaction method. According to subjective results, it was considered as the most appropriate because it allows the manipulation of objects in a way that is similar to the use of bare hands. In the objective results, the mouse interaction method was the most accurate.